Patient assessment of cosmetic outcome after craniotomy for intracranial tumor surgery - Amalie Sofie Vagner Uggerly; Morten Winkler Møller; Elin Eriksen; Carsten Reidies Bjarkam; Frantz Rom Poulsen (Interdisciplinary Neurosurgery, 2023)
Background: Intracranial tumors are commonly approached through a craniotomy, and the bone flap is later reattached with plates and screws. The gap created around the bone flap may cause the skin to submerge, potentially influencing the facial and head aesthetic appearance. The aim of this study was to examine patient satisfaction with cosmetic outcome after craniotomy for intracranial tumor resection. Methods: In a prospective questionnaire-based study, patients were asked to report their degree of satisfaction with the scar and overall cosmetic appearance, and the extent of change to their facial appearance using 0–10 rating scales. The questionnaire was sent six months after surgery to patients undergoing first-time craniotomy for tumor resection at either of two neurosurgical departments. Results: Of the 70 patients included in the study, 49 (70%) completed the questionnaire. Median scores were 9.3 for satisfaction with the scar and 9.0 for overall cosmetic satisfaction (a score of 10 reflected highest satisfaction). The median score was 1.7 for degree of change in facial appearance (a score of 0 reflected no change). However, 24.5% of patients reported major alterations to facial appearance. Satisfaction levels were similar by age, sex, and tumor type, but patients with occipital craniotomies were less satisfied with the overall cosmetic result than those with temporal craniotomies. Conclusion: Most patients were satisfied with the cosmetic outcome of the craniotomy, but a considerable proportion reported major facial alterations. While the level of overall cosmetic satisfaction did not differ according to age, sex, or tumor type, the location of the craniotomy seemed to be a factor in satisfaction with the aesthetic outcome. Further studies are needed to investigate how the cosmetic result from craniotomy could be improved from the patient's perspective.